2012
DOI: 10.1111/j.1745-3933.2012.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation functions for extended mass galaxy clusters

Abstract: The phenomenon of clustering of galaxies on the basis of correlation functions in an expanding Universe is studied by using equation of state, taking gravitational interaction between galaxies of extended nature into consideration. The partial differential equation for the extended mass structures of a two-point correlation function developed earlier by Iqbal, Ahmad and Khan is studied on the basis of assigned boundary conditions. The solution for the correlation function for extended structures satisfies the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The two particle correlation function in this context is the probability of finding two particles together within a given volume. The specific form for this correlation function has been defined by (Iqbal et al ). ζntrue‾,T,r=ctruenZ/3TZNrZ()r2+ϵ2Z/2 which then yields (for structureless galaxies in the ϵ → 0 limit) (Yang et al 2011; Saslaw & Ahmed ).…”
Section: Methods To Study the Gravitational Phase Transition Of Galaxymentioning
confidence: 99%
“…The two particle correlation function in this context is the probability of finding two particles together within a given volume. The specific form for this correlation function has been defined by (Iqbal et al ). ζntrue‾,T,r=ctruenZ/3TZNrZ()r2+ϵ2Z/2 which then yields (for structureless galaxies in the ϵ → 0 limit) (Yang et al 2011; Saslaw & Ahmed ).…”
Section: Methods To Study the Gravitational Phase Transition Of Galaxymentioning
confidence: 99%
“…In order to understand the simple formalism of peculiar velocity, we make use of quasi equilibrium thermodynamics in which quasi equilibrium evolution takes place through a sequence of quasi equilibrium states whose properties change with time (Saslaw & Hamilton. 1984, Saslaw et al 1990, Ahmad et al 2002, Iqbal et al 2006and Iqbal et al 2012. cluster size R, the average kinetic energy of peculiar motions of N galaxies in a cluster can reasonably be connected with average kinetic temperature T of a cluster (Saslaw.…”
Section: Peculiar Motion Of Galaxy Clustersmentioning
confidence: 96%
“…The observational studies (Rines & Diaferio 2006), N-body simulations (Wojtak et al 2005;Mamon et al 2004;Cuesta et al 2008) and a combination of both (Mahajan et al 2011) have shown that virialized clusters in gravitating systems are surrounded by infall zones from which most of the galaxies move into the relaxed cluster, as is evident from the earlier result of (Gunn & Gott 1972). In order to understand the simple formalism of a peculiar velocity, we make use of quasi-equilibrium thermodynamics in which quasi-equilibrium evolution takes place through a sequence of quasi-equilibrium states whose properties change with time (Saslaw & Hamilton 1984;Saslaw et al 1990;Ahmad et al 2002;Iqbal et al 2006Iqbal et al , 2012.…”
Section: Peculiar Motion Of Galaxy Clustersmentioning
confidence: 99%
See 2 more Smart Citations